Breastfeeding, pregnant, and non-breastfeeding nor pregnant women's food consumption: A matched within-household analysis in India - Fledderjohann, J; Vellakkal, S; Stuckler, D (Elsevier, 2015)
Objective: Promoting breastfeeding is major maternal and child health goal in India. It is unclear whether mothers receive additional food needed to support healthy breastfeeding. Methods: Using the latest National Family and Health Survey (2005-2006), we applied multilevel linear regression models to document correlates of nutrition for (n=20,764) breastfeeding women. We then compared consumption of pulses, eggs, meat, fish, dairy, fruit, and vegetables across a sample of breastfeeding, non-breastfeeding/pregnant (NBP), and pregnant women (n=3,409) matched within households and five-year age bands. We tested whether breastfeeding women had greater advantages in the 18 high-focus states of India’s National Rural Health Mission (NRHM). Results: Vegetarianism, caste, and religion were the strongest predictors of breastfeeding women’s nutrition. Breastfeeding women had no nutritional advantage compared to NBP women, and were disadvantaged in their consumption of milk (b=-0.14) in low-focus states. Pregnant women were similarly disadvantaged in their consumption of milk in low-focus states (b=-0.32), but consumed vegetables more frequently (b=0.12) than NBP women in high-focus states. Conclusions: Breastfeeding women do not receive nutritional advantages compared to NBP women. Targeted effort is needed to assess and improve nutritional adequacy for breastfeeding Indian women.